Features of building the knowledge base of standard methods of examination - Вдовиченко, Ирина Никифоровна (Eastern-European Journal of Enterprise Technologies, 2010)
The structure of the database of standard techniques of examine is considered. The advantages of using a knowledge base for selecting the optimal technique are noted. The choice of a product model as a model of knowledge representation is proved. The variant of the initial facts for search production rules is offered.